Sensor Fault Diagnosis and System Reconfiguration Approach for an Electric Traction PWM Rectifier Based on Sliding Mode Observer - Xia, Jinhui; Guo, Yuanbo; Dai, Bijun; Zhang, Xiaohua (IEEE transactions on industry applications, 2017)
Single-phase pulse-width modulation (PWM) rectifier is commonly used in a high-speed railway electric traction system. Occurrence of unexpected failure in the sensors of the detection system may lead to feedback values deviation and system degradation, which can be extremely detrimental to the operation safety of the electric locomotive. This paper presents a fast and reliable fault diagnosis and fault resilient control strategy for catenary current and dc-link voltage sensor faults in the control system for an electric traction single-phase PWM rectifier. Sliding mode observers are designed to produce analytical redundancy. In order to avoid unobservable states and fluctuation introduced by discrete dynamics in observer design, a novel description for switching variables is presented in system modeling. Normalized residuals are generated using measured and observed values. The fault diagnosis unit proposed can detect and isolate three types of sensor faults online by comparing residuals with thresholds. System reconfiguration is realized by substituting the observed values for the information of faulty sensors. Simulation and experimental results are demonstrated to validate the effectiveness of the strategy.